Thymol combined with SAEW for the eradication of mature Pseudomonas aeruginosa biofilms and reduction of bacterial virulence - Zhexiao Ma; Changrui Qian; Zeyong Zhong; Zhuocheng Yao; Congcong You; Jianming Cao; Cui Zhou; Jianzhong Ye (Frontiers in Microbiology, 2025)
IntroductionBiofilms formed by Pseudomonas aeruginosa (P. aeruginosa) are a major challenge in clinical settings due to their resilience and contribution to persistent infections, especially in patients with indwelling medical devices. There is an urgent need for effective strategies to disrupt mature biofilms and control associated infections.MethodsThis study investigated the combined antibacterial activity and mature biofilm eradication efficacy of slightly acidic electrolyzed water (SAEW) and thymol against P. aeruginosa PAO1 through mature biofilm removal assays. The underlying antibacterial mechanism was explored by measuring intracellular reactive oxygen species (ROS) levels. The impact of the combined treatment on the expression of PAO1 virulence genes was assessed using RT-qPCR. Additionally, the safety of the combination was evaluated through acute dermal toxicity and ocular irritation tests in mice.ResultsThe combination of thymol and SAEW effectively disrupted mature biofilms, significantly reduced bacterial load on medical catheters, and enhanced ROS production. Furthermore, the treatment downregulated key virulence genes, lasA and lasB, which are critical for elastin degradation and pathogenicity. Safety assessments confirmed no acute skin or ocular toxicity, indicating its suitability for clinical applications.DiscussionThymol-enhanced SAEW shows great potential as a safe and effective strategy for biofilm eradication and infection control, paving the way for innovative approaches to combat antimicrobial-resistant pathogens in healthcare settings.